Too-big-to-fail and funding costs: A repository of research studies - Claudia M. Buch; Angélica Dominguez-Cardoza; Martin Völpel (Deutsche Bundesbank, 2021)
Systematic reviews of evaluation studies benefit policy discussions and academic research and are used in many disciplines. In March 2019, the Bank for International Settlements (BIS) thus launched FRAME, a public, online and interactive repository of studies on the effects of financial regulations with an initial focus on the Basel III reforms. This paper describes an extension to this repository with research on the impact of too-big-to-fail (TBTF) reforms on banks' funding costs. One objective of post-crisis financial sector reforms has been to internalize systemic risk externalities through changes in the funding costs of banks that are classified as being systemically important. The FRAME repository now contains studies on the funding costs of systemically important banks (SIBs), and it currently comprises over 280 quantitative impact estimates from 25 studies.
Keywords: E44; G01; G18; G21; G28; 330; Financial sector reforms; too-big-to-fail; banks' funding costs